Pharmacogenomics of risperidone in autism spectrum disorder: a minireview - Honório, Caroline Rafaelli de Lima; Bobadilha, Beatriz Gafanhão; Conscetta, Melina Pinheiro; Silveira, Felipe De Mello; Durigon, Francisco; Planello, Aline Cristiane (Frontiers in Pharmacology, 2026)
Risperidone is one of the most widely prescribed antipsychotics for the management of irritability and associated behavioral symptoms in autism spectrum disorder (ASD), yet clinical response and adverse-effect risk vary widely among individuals. Pharmacogenomic (PGx) research has sought to explain this variability, with accumulating evidence pointing to contributions from metabolic, transporter, and neurotransmitter pathways. In this narrative minireview, we synthesize current findings on PGx factors influencing risperidone outcomes in children and adolescents with ASD. CYP2D6 emerges as the most robust predictor of pharmacokinetics and toxicity, while pharmacodynamic associations involving dopaminergic, serotonergic, and metabolic pathways in genes such as ABCB1, DRD3, HTR2A, HTR2C, and LEP remain inconsistent and largely derived from small cohorts. We also discuss methodological challenges in assessing treatment response, current clinical guidelines, barriers to implementation, and emerging approaches including polygenic models, pharmacoepigenomics, and machine learning. Together, the available evidence points to both the promise and the limitations of PGx in guiding safer and more individualized risperidone therapy in ASD.